(untitled) (Environmental Smoke, 2025)
This article sought to identify environmental education initiatives focused on biodiversity conservation that exist in the coastal and marine zone of Paraíba State (Northeastern Brazil), evaluating their foundations through the construction of scientific-pedagogical models. Being presented in a transversal and multidisciplinary way, in formal and non-formal education, integrated with government policy in its different spheres (national and international), with the target audience involving the entire society. Advances in environmental education and their impact on the resolution of the main environmental conflicts in the marine and coastal areas are discussed, in particular, the protection of living beings and marine natural resources. The need for ecological literacy in the twenty-first century was verified, and its importance in the formation of ecological awareness and the exercise of environmental citizenship, placing emphasis on current processes in Paraíba. As a result of the Discipline of Environmental Education for Biodiversity Conservation of the Post-Graduation Program in Ecology and Environmental Monitoring (PPGEMA) at the Federal University of Paraíba (UFPB), subsequently counting on the collaboration of the Institute of Research and Action (InPact), of the Guajiru Association, of the SISFAUMAR-PB (Paraíba Marine Fauna Monitoring System) and the Paulo Young Invertebrate Laboratory of the Department of Systematics and Ecology of the Federal University of Paraíba (LIPY-DSE-UFPB), it is expected to contribute to the knowledge, information and instruments that assist in environmental management and the implementation of government policies for the coastal and marine environment of South Atlantic America.